2022
DOI: 10.3390/cancers14040998
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Malignant Adnexal Tumors of the Skin: A 12-Year Perspective

Abstract: Malignant adnexal cancers of the skin—extremely rare neoplasms—are mostly reported as non-symptomatic, slow-growing nodules. These carcinomas occur mainly in the middle-aged (50–60 years of age); they are mostly localized on the upper part of the body and are locally aggressive, infiltrate surrounding tissue, and metastasize to regional lymph nodes. The patients’ outcomes depend on multiple prognostic factors, including the size of the primary tumor and its mitotic count. Surgical resection of the primary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…The stability and management of eccrine carcinoma with combined radiotherapy and chemotherapy has been reported in the literature, especially when surgery is not an option [3] [7] [8]. Marcin et al reported the case of a patient who received chemotherapy combined with CAV (vincristine doxorubicine cyclophosphamide) and EP (etoposide cisplatin) for the metastatic form [9]. Joseph et al reported in response to taxane treatment in a patient with a metastatic eccrine tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The stability and management of eccrine carcinoma with combined radiotherapy and chemotherapy has been reported in the literature, especially when surgery is not an option [3] [7] [8]. Marcin et al reported the case of a patient who received chemotherapy combined with CAV (vincristine doxorubicine cyclophosphamide) and EP (etoposide cisplatin) for the metastatic form [9]. Joseph et al reported in response to taxane treatment in a patient with a metastatic eccrine tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Sebaceous carcinoma is part of the group of Malignant Adnexal Tumors of the Skin (MATS) and it is a rare and aggressive tumor that accounts for less than 1% of all cutaneous tumors, but even despite that, it is the most common type among cutaneous adnexal tumors [3,7,[12][13].…”
Section: Discussionmentioning
confidence: 99%
“…About 25% of its cases are extraocular and are generally located on the head and neck, although references are pointing that the following are also possible locations for the disease: parotid, breast, ovary, prostate, trunk, and extremities [2,4,7,9,12,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations